Eksperimen Pembelajaran Contextual Teaching And Learning Dan Cooperative Learning Type Think Pair Share Terhadap Kemandirian Belajar Siswa Ditinjau Dari Motivasi Belajar Pada Siswa Kelas IV SD Negeri Tempel Surakarta - Wibawakusuma, Kurnianingtyas, Prof.Dr. Sutama, M.Pd, Dr.Suyatmini,SE.,M.Si (2016)
Kurnianingtyas WK. Q100130016. Experiment of Learning Contextual Teaching And Learning And Cooperative Learning Type Think Pair Share Towards Self-reliance In Terms Of Student Learning Motivation of Learning at Grade IV SD Negeri Tempel Surakarta. Thesis. Education Management Post Graduate. Muhammadiyah University Surakarta. 2015 This research aims to: 1) analyzes the differences learning Contextual Teaching and Learning and Cooperative Learning Types Think Pair Share against the independence of the study. 2) analyzes the differences in terms of learning motivation of the independence of the study. 3) Analyzing the interaction of learning strategies (Contextual Teaching and Learning and Cooperative Learning Types Think Pair Share) and learning motivation towards learning independence. This research uses a type of experimental research, design research using quantitative methods. The population in this research is the whole grade IV SD Negeri Tempel Surakarta in academic year 2014/2015. The number of samples in the study was 37 students consisting of Class IV with as many as 18 students and Class IV B as much as 19 students. Data collection techniques using observation and question form. Data analysis techniques using analysis of two lines. Based on the results of data analysis and discussion of the obtained conclusions that: there is a significant difference of learning Contextual Teaching and Learning and Cooperative Learning Types Think Pair Share towards the independence of learning in students of class IV SD Negeri Surakarta Outboard Years Lessons 2014/2015. It shows that the independence of student learning that is taught by learning Contextual Teaching and Learning higher or better than the lesson that students learned self-reliance with Cooperative Learning Types Think Pair Share. There is a difference in terms of learning motivation of independence studied in grade IV SD Negeri Surakarta Outboard Years Lessons 2014/2015. This shows that students who have a high learning motivation also has a high learning independence anyway. There are interaction learning strategies (Contextual Teaching and Learning and Cooperative Learning Types Think Pair Share) and motivation towards learning the independence of learning in students of class IV SD Negeri Surakarta Outboard Years Lessons 2014/2015. Thus between learning and the learning motivation of students in systematic interactions occur affecting the independence of the student learning Keywords: learning independence, learning motivation, Cooperative Learning Types Think Pair Share